THE RELATIONSHIP OF KNOWLEDGE AND ATTITUDES OF ADOLESCENT WOMEN TO PREVENTION MEASURES OF LEUCHING IN NAGORI RABUHIT, GUNUNG MALIGAS SUBDISTRICT SIMALUNGUN DISTRICT 2016 - Yunardi (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2021)
Based on the findings of the researchers that there were 5 young women in Nagori Rabuhit, Gunung Maligas District, Simalungun Regency, experiencing vaginal discharge. This research was conducted to find out whether there is a relationship between the knowledge and attitudes of young women towards the prevention of vaginal discharge in Nagori Rabuhit, Gunung Maligas District, Simalungun Regency in 2016. This type of research is descriptive with the population in this study being all young women in Nagori Rabuhit, Gunung Maligas District, Simalungun, namely as many as 108 people who were sampled as many as 85 people using the simple random sampling technique, which is a simple random sampling method. The results of this study the majority have knowledge.